Business statistics - Chong, Choo Wei; Sambasivan, Murali; Leng , Goh Poi (Prentice Hall, 2002)
This book, Business Statistics, Second Edition, is intended for an undergraduate course in Business Statistics. It assumes familiarity with introductory ideas on probability and probability distributions.This book is based on the syllabus meant for undergraduate students at UPM.It includes material on all the topics of Business Statistics. This book does not replace the existing textbook by Richard I.Levin and David S. Rubin. It merely supplements the textbook material.A book of this nature helps students 1. to quickly understand a topic before going 'deep' into it and 2. to quickly revise the syllabus material before the exams.